Robust Simultaneous Fault Detection and Control Approach for Time-Delay Systems. Issue 21 (2015) - Soltani, H.; Naoui, S. Bel Hadj Ali; Aitouche, A.; Harabi, R. El; Abdelkrim, M.N.
Abstract: The problem of Robust Simultaneous Fault Detection and Control (RSFDC) approach for a class of uncertain system with state time delay, was investigated in this paper. Based on a dynamic filter with state feedback controller, H ∞ formulation of the RSFDC problem was presented. In fact, the idea given herein, is based on applying the advantages of dynamic observers, which lead to some sufficient conditions for solvability of the RSFDC problem in terms of LMI feasibility conditions. The effectiveness of the design technique is illustrated via an example.